Interest rate snapback and the impacts on the Irish economy - Paul Egan; Eoin Kenny; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2023)
In this paper, we explore the impact of recent interest rate increases on the Irish economy and chart out the potential impact using scenarios for the period 2023- 2025. We use the COSMO macroeconometric model of the Irish economy to test the impacts through credit markets and the real economy, separately modelling the impact on consumer, corporate and mortgage markets. We also use micro data from the Household Finance and Consumption Survey (HFCS) to test the impact on mortgage affordability of the interest rate increases. Our scenarios are drawn from the European Banking Authority (EBA) stress tests which provide base and adverse outcomes for the policy rate. These are compared to a pre-Ukraine war baseline. We find notable effects on the mortgage market and house prices as well as sizable impacts on key macroeconomic aggregates such as investment, consumption and output. We also observe an increase in housing payment to income ratios but no major increase in mortgage affordability distress as measured by the residual income approach.
Keywords: 330; Zins; Geldpolitische Transmission; Wirkungsanalyse; Hypothek; Markt; Szenariotechnik; Makroökonometrie; Irland